How Does Environmental Irresponsibility Impair Corporate Reputation? A Multi‐Method Investigation. (31st March 2016) - Lin, Han; Zeng, Saixing; Wang, Liangyan; Zou, Hailiang; Ma, Hanyang
Abstract: Sustainable development has received worldwide attention. Recent studies on corporate environmental behavior have called for research from the specific stakeholder's perspective (i.e., consumer) on the topic of going green. Based on reputation theory, this paper employed a secondary data analysis and three experiments to highlight the influence of environmental irresponsibility on corporate reputation perceived by consumers. Coherent results showed that environmental irresponsibility negatively affected corporate reputation and perceived corporate ethics served as a mediator. Furthermore, corporate social responsibility (CSR) activities could alleviate the harmful consequences of irresponsible behavior by moderating the mediating role of perceived corporate ethics in determining the influence of environmental irresponsibility. Copyright © 2016 John Wiley & Sons, Ltd and ERP Environment